Price Volatility in Food and Agricultural Markets : Policy Responses - FAO; IFAD; IMF; OECD; UNCTAD; WFP; World Bank; WTO; IFPRI; United Nations High Level Task Force on Global Food and Nutrition (World Bank, Washington, DC, 2017)
The approach taken in this report reflects the view of the collaborating international organizations that price volatility and its effects on food security is a complex issue with many dimensions, agricultural and non-agricultural, short and long-term, with highly differentiated impacts on consumers and producers in developed and developing countries. The report begins with a discussion of volatility and of the ways in which volatility affects countries, businesses, consumers and farmers. Lessons learned from recent experiences are briefly reviewed as well as the factors determining likely levels of volatility in future. This report offers suggestions for a systematic and internationally coordinated response building on the lessons learned as a result of the 2007-2008crisis. It is important to distinguish between policy options designed to prevent or reduce price volatility and those designed to mitigate its consequences. Both types of intervention are explored in detail. Scope is identified for actions at individual, national, regional and international level. Some would help to avert a threat; others are in the nature of contingency plans to improve readiness, while still others address long-term issues of resilience. Finally, the report explores mechanisms of international cooperation to implement this report's recommendations and to monitor progress.